Pelaporan Aset Barang Milik Negara terhadap Langkah-Langkah dan Kendala Penggunaan Aplikasi SIMAK BMN pada Balai Pengembangan Kompetensi PUPR Wilayah I Medan - Dinda Ardena; Kusmilawaty Kusmilawaty (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
AbstractThe purpose of this research is to find out the steps and obstacles to the use of SIMAK BMN implementation.  The research methodology used is a descriptive qualitative approach.  Data was collected using interviews with the staff of the BMN analyst section.  The results of this study were obtained based on the output of research that had been carried out at the Regional I PUPR Competency Development Center in the administrative process through a series of steps that were passed, as well as the obstacles faced by SIMAK-BMN users, namely: there was no notification of changing the SIMAK BMN version, and internet network disruption. Keywords: Accounting System, Management Information System, Asset Reporting.